Branch portal vein pyaemia secondary to amoebic liver abscess. (8th June 2015) - Kenny, Conor; Sohan, Oliver; Murray, Lois; Fox, Thomas Peter
Abstract : We describe a case of a young returning traveller who contracted amoebic dysentery while visiting India. She presented to a major London Hospital several months later with features suggestive of amoebic liver abscesses, a known sequelae of amoebiasis. MRI with intravenous contrast demonstrated an area of likely occlusion of the portal vein. The patient was treated with intravenous metronidazole for 10 days followed by diloxanide furoate, an intraluminal agent. The largest abscess was drained acutely under ultrasound guidance. The portal vein occlusion was treated medically without the use of anticoagulation. A repeat ultrasound at 6 weeks post-treatment confirmed patency of the portal vein indicating spontaneous recanalisation with antimicrobial therapy alone.